Le guide touristique: lieu de rencontre entre lexique et images du patrimoine culturel. Vol. I - Flinz, Carolina; Carpi, Elena; Farina, Annick (Strumenti per la didattica e la ricerca, 2018)
This book is the first volume of a collection of articles devoted to the tourist guide as a meeting place between lexicon and images of cultural heritage, a work resulting from the conference which took place on June 11 and 12, 2015 in Pisa and Florence, organized by the Research Unit Lessico dei Beni Culturali. The texts presented are the result of a joint reflection by specialists from different fields: linguistics, art history, architecture, photography, literature and geography to name a few. The two volumes analyze the tourist guide and the other works that accompany the trip as places of creation and transformation of the experience of real or virtual travel, participating as such in the creation of the tourist imaginary of places and cultural objects they describe.